PREVENTION OF TERRORISM ATTACKS THROUGH ENVIRONMENTAL DESIGN IN INDONESIA AIRPORT - Wahyudi, Rizki; Priyanto, Sapto, Mr. (Journal of Terrorism Studies, 2022)
This research previously identified civil aviation as a vulnerable and appealing target. Terrorism-related airport security concerns have gained much attention since the 9/11 attacks. Terrorist assaults against flights, airports, passengers, crew, and cargo continue to pose a severe threat to human and national security worldwide. The X Indonesia International Airport is a civil enclave airport that offers the concept of Crime Prevention Through Environmental Design to combat these attacks and threats (CPTED). This article aims to provide an overview of airport security management and present a CPTED concept for avoiding a terrorist assault and threat. This paper employs a descriptive qualitative approach with in-depth interviews and a literature review as a data-gathering strategy. The result depicts the CPTED concept developed to prevent terrorism: access control, surveillance, and territoriality. Furthermore, it is believed that collaboration in security management would be ideal in carrying out CPTED to eradicate terror elements and establish a sense of security in public venues. Thus, it is envisaged that the creation of this idea would help the X International Airport region build a sense of security and stability and eradicate terror fears.